Behaviour and physiological effects of transmitter attachments on a captive harbour porpoise (Phocoena phocoena) - Geertsen, B. M.; Teilmann, J.; Kastelein, R. A.; Vlemmix , H. N. J.; Miller , L. A. (J. Cetacean Res. Manage., 2023)
A captive harbour porpoise (Phocoena phocoena) was monitored for 80 consecutive days, 10 days before attachment of a satellite dive recorder and a VHF-radio tag, 30 days during attachment and 40 days after removal of the transmitters. Dive data recorded by the satellite transmitter was collected during the attachment. Daily food intake was measured and each week the porpoise was taken out of the water for a physical examination. Behavioural observations logged on the handheld computer showed an immediate effect of the tagging in time spent resting at the surface (logging), which was four to six times higher on the day of attachment. Digital video recordings showed a significant increase in the mean duration of rolls at the surface immediately after attachment. The mean duration of dives was shorter before attachment than both after the tagging and after removal of the transmitters. Furthermore the frequency of surfacings farthest away from where the porpoise was taken out of the pool for tagging, was highest the first five days following the tagging. Dive data from the satellite tag showed a semidiurnal diving pattern, with increased mean dive depth in the first 24 hours after attachment. The heart rate was fairly constant during the tagging, but the mean heart rate increased significantly from 161 beats per minute (bpm) to 180 bpm after the first hole in the dorsal fin was made. The body weight of the porpoise increased up to the time of tagging (16 May 2000), after which it decreased until six days prior to release (28 July 2000); this was probably due to the seasonal trend in blubber thickness of harbour porpoises rather than an effect from the tagging. After one month of attachment, a reaction occurred around the frontal pinhole and the transmitters were removed. This reaction was probably due to drag from two tags and seaweed attached to the tags during the last part of the attachment period. After the tags were removed epithelia closed the pinholes after two days.